The taxonomy and morphological and anatomical differentiation of populations of Leiothrix crassifolia (Eriocaulaceae) - Scatena, V. L.; Giulietti, A. M. (Springer, 1996)
The morphological and anatomical leaf and scape differentiation of Leiothrix crassifolia is analysed and classified into seven types (I, II, III, IV, V, VI, Vn). The species has a relatively wide distribution in the campo rupestre of Minas Gerais in Brazil. Variation in the isolated populations on different mountain ranges is complex, does not follow a clear geographical pattern, and defies taxonomic classification. L. nubigena and L. obtusifolia are included in L. crassifolia.
Keywords: Eriocaulaceae; Leiothrix crassifolia (L-nubigena, L-obtusifolia); morphological and anatomical variation; geographical differentiation; taxonomy; flora of 'campos rupestres'; Brazil